Risk factors associated with blood pressure variation in sickle cell disease in Cameroon - Nguweneza, Arthemon (Department of Clinical Laboratory Sciences, 2025)
Background: In SCD patients, studies have shown that increased Blood Pressure (BP) is associated with higher risk of stroke and mortality, even in a range of systolic BP(SBP) and diastolic BP(DBP) that are considered relatively normal for the general population (i.e., lower than 140 mmHg). SCD patients, generally, have lower systolic, diastolic, and mean BP compared to age and sex-matched controls. Relative Systemic Hypertension (RSH) for SCD patients is defined as BP ranging from 120–139/70–89 mmHg, and Systemic Hypertension for SCD patients with BP above 140/90 mmHg. BP may be a potential modulator of clinical severity in SCD patients. BP is a heritable trait with estimates indicating that 30–70% of the trait variance is attributable to genetic variation. A recurrent deleterious and loss of function mutations in genes associated with lowering BP, e.g., variants in CLCN6, have been recently associate with long survival in SCD in Cameroon. Additionally, demographic, biological, and anthropometric factors have been reported to be associated with BP in SCD patients. Understanding the aetiology of BP variation in SCD patients and assessment of up-to-date evidence is key to early prediction of potential BP-related complications in SCD patients. Early prediction of BP-related complications in SCD patients could lead to better prevention and treatment of SCD and its associated causes of mortality. Herein, we investigated (clinical, genetic, and epidemiological) risk factors associated with RSH or Systemic Hypertension in SCD patients in Cameroon to gain insight into the pathophysiology of BP variation in this disease in an African setting. Objectives: 1) A systematic review and meta-analysis on BP variation (Normal, Relative Systemic Hypertension(RSH) and Hypertension) among SCD patients; 2) Investigate clinical and epidemiological risk factors for RSH and Systemic Hypertension in 815 SCD patients in Cameroon; 3) Identification of genetic variants associated to BP variation in SCD patients in Cameroon using a Genome-wide Association study; 4) Functional analysis on pathways and mechanisms underlying BP variation in SCD patients. Methods: Systematic review and meta-analysis: A protocol was developed and registered with the International Prospective Register of Systematic Reviews (PROSPERO), registration number CRD42020168798. A search was conducted on the following electronic databases: PubMed, Scopus, and Web of Science. The Preferred Reporting Items for Systematic Reviews and Meta- analysis (PRISMA) served as a template for reporting the review and meta-analysis. Independently, in collaboration with another reviewer, we screened studies, extracted relevant data, assessed methodological quality and risk of bias on each included study. A retrospective analysis to investigate risk factors associated with RSH or Systemic Hypertension in SCD patients in Cameroon. Participants who had incomplete/out of range BP readings were excluded from this analysis. Categorical variables were compared using Chi squared test or Fisher exact test if the expected count in a cell was less than five while continuous variables were compared according to BP category with the Kruskal–wallis test. Multivariate multinomial logistic regression modelling was used to examine the effects of the demographic, anthropometric, clinical, and laboratory factors to determine the potential independent risk factors for RSH and Systemic Hypertension. A final model was created that included all the predictors and interactions that were significantly associated at the level of P < 0.001) and gender (P = 0.022) were significantly different across the BP categories, with age increasing with BP. Weight (P < 0.001), height (P < 0.001), BMI (P < 0.001), pulse pressure (P = 0.020), history of stroke (P = 0.012), haemoglobin (P = 0.002), red blood cell count (P = 0.031), creatinine (P < 0.001), and eGFR (P= 0.002) were also significantly different across the three BP categories. Among SCD patients, univariate analyses indicated that these variables were significantly more common risk factors for higher BP values among patients with RSH than those with normal BP: Age (P < 0.001), patients >18 years (P < 0.001), weight (P < 0.001), height (P < 0.001), BMI (P < 0.001), pulse pressure (P = 0.046), creatinine (P < 0.001), eGFR (P < 0.001) and haemoglobin (P = 0.020) . Multivariate analyses found that age [OR = 1.02, (95% CI = 1.01–1.05), P = 0.021], creatinine [OR = 1.310, 95% CI = 1.05–1.63, P = 0.016], BMI [OR = 1.09, (95% CI = 1.03– 1.16), P = 0.002] were independent risk factors for high BP values in SCD patients with RSH compared with SCD patients with normal BP values. Genome-wide analysis and meta-analysis: For SBP, we found two genetic loci including independent and suggestive SNPs. The first locus was found in RP11-727A23.5 on chromosome 11 (rs146072506, P=4.88x10-08), the second locus was found on DLGAP1 gene on chromosome 18 (rs35715722, P=3.408x10-08). Two other SNPs were found in the intergenic regions. For DBP, the only significant SNP was in the intergenic region. Additionally, we found one SNP (rs186536474, p=8.90x10-09) located on GPR39 gene on chromosome 2 with a statistically significant p-value associated with BMI. Identified variants in intergenic regions may play a role in specific genes regulating BP or BMI. The meta-analysis of the Cameroon SCD cohort and Silent Infarct Transfusion Trial (SITT) cohorts, and African American cohort of SCD patients, did not find significant SNPs. After performing genetic analysis and Gene-set analysis with none of the identified genes or gene-set reached a significant threshold. Additionally, tissue expression analysis did not reach significant thresholds. Conclusion: This is the first in-depth investigation of the non-genetic and genetic risk factors associated with BP variation (RSH or Systemic Hypertension) in SCD patients in Africa, i.e., Cameroon. Age, male gender, BMI was found to be statistically significant independently associated factors of RSH and Hypertension in the SCD patients in Cameroon. The GWAS analysis identified a few SNPs which were statistically associated with BP and BMI in Cameroonian SCD patients. These SNPs require follow up studies in larger SCD cohorts. Tailored interventions that consider both genetic and non-genetic risk factors have potential to lead to better management of BP pressure in SCD patients and prevent possibly prevent development of severe SCD complications.